Community Perception of the Todilaling Grave in Napo Village, Limbor Districy, Polewali Mandar - Musyarif Musyarif; Ahdar Djamaluddin; Rezki Kasim (Universitas Muhammadiyah Enrekang, 2024)
The Todilaling Tomb is the Tomb of the first King of Balanipa. Pilgrimages to the Todilaling Tomb have been carried out for generations, but some people make pilgrimages to the Todilaling Tombto ask for blessings. This gives rise to differences in perception in society. The sub-problems in thisresearch are 1) what was Todilaling's policy as the first King of the Balanipa Kingdom in PolewaliMandar Regency, 2) what was the public's perception of the Todilaling Tomb in Napo Village, LimboroDistrict, Polewali Mandar Regency. Study This aim For know policy Todilaling as the first King of theBalanipa Kingdom and perception public towards the Todilaling Grave . This research is study fieldwith use approach Qualitative. The results of this research show that, 1) during Todilaling's reign therewere several policies issued, including the policy of changing the Kingdom's government system, beforeTodilaling Reign condition become a King does not own condition after Todilaling come policies issuedis All King selection systems are based on lineage, which means that only the King's descendants havethe right to become the next King. Then the second policy is change Community customs which isinhumane , 2) The Tomb of King Todilaling creates a perception among the public, there are people whobelieve that if they want something they can ask at the Tomb of Todilaling, then there are also peoplewho don't believe it because they think this act is an idolatrous act.